Nominal countability processing in four anglophone patients with aphasia: The deficit in the use of uncountable nouns - Martínez Almagro, Lucas Jesús; Taillefer, Lidia (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study investigates nominal countability processing. It presents further evidence in favour of a possible influence of the semantic number in uncountable nouns processing in four patients diagnosed with Broca’s aphasia, whose native language is English. This suggests that the processing of these nouns would be a semantic and syntactic hybrid. Moreover, it corroborates as previous studies, a specific deficit in uncountable nouns grammar.